Comparative analysis of temporal parameters of different techniques of the freestyle flip turn - Pereira, S. M.; Ruschel, C.; Souza, T. G.; Araujo, L. G.; Goncalves, P.; Fernandes, R.; Roesler, H.; Vilas-Boas, J. P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This study aimed to describe and compare temporal parameters of four different turning techniques of Freestyle swimming flip turn. 17 national level swimmers participated in this study. After practicing sessions, the swimmers performed three times each of the four analyzed techniques. Performance was videotaped using six video cameras and the analyzed variables were: rolling time, wall contact time, pushing time, gliding time and total turn time. No differences were found between the techniques for any variable. Apparently, the choice of the technique can be made accordingly to the swimmer's subjective preference, or based on the objective performance differences casuistically sustained. However, future studies are needed and additional performance indicators should be analyzed to provide a better understating regarding the different techniques